Complexation and Colour Stability of Anthocyanins from the Extracts of Java Plum Fruits (Syzygium cumini) with Selected Metal Cations (Al3+, Fe3+, and Ca2+) at Various pHs - Wathon, Muhammad Hizbul; Susilowati, Endang; Ariani, Sri Retno Dwi; Sari, Latifah (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Anthocyanins are highly coloured polyphenols, a class of flavonoids, which are natural, non-toxic, and water-soluble compounds. Because of that, anthocyanins have been used in numerous applications, such as natural colorants for foods, beverages, and textiles. However, anthocyanins have some drawbacks regarding their stability towards temperature, pH, and light, leading to degradation. One method to improve anthocyanins’ stability can be achieved through a complexation reaction of anthocyanins with metal cations. Thus, this study aimed to investigate the stability and colour profiles of anthocyanins extracted from Java Plum fruits (Syzygium cumini) complexed with Al3+, Fe3+, and Ca2+ ions in pH 1-12. Previously, anthocyanins from Java Plum fruits have been identified by LC-MS as cyanidin-3-O-glucoside ([M]+, m/z 449.3), delphinidin-3-O-glucoside ([M]+, m/z 465.3), and petunidin O-glucoside ([M]+, m/z 479.3). The ATR FTIR was also performed to confirm the functional group of anthocyanins. The colour of each solution at different pH was evaluated by UV-Vis Spectrophotometer at 200-800 nm. Complexation of anthocyanins with Al3+, Fe3+, and Ca2+ ions showed various colours at different pHs. The complexation of anthocyanins with Al3+ at pH 4-5 developed a blue colour. The intensity of the blue colour increases with an increase in Al3+ ion concentration. This investigation showed the potential application of anthocyanin-metal chelation for the textile industry due to the range of colour produced. Furthermore, the complexation of anthocyanins to produce blue colour can be an alternative in food industries as this colour is difficult to obtain in acidic pH.